2007
DOI: 10.1258/000456307779595896
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of serum testosterone in women; what should we do?

Abstract: AddressesAll immunoassays for female serum testosterone give falsely high results in some samples. The effect is variable and cannot be predicted for any given sample. Inaccurate calibration or interference by cross-reacting substances is almost certainly the cause of the problem, but for many immunoassays, the exact nature of the interferent is not known. Some of the interference can be removed by employing an extraction step prior to immunoassay. The advent of fast simple and sensitive liquid chromatography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 35 publications
0
23
0
5
Order By: Relevance
“…None of the immunoassays investigated (Table 1) used an extraction step, as a prescribed procedure, before analysis. We extracted testosterone using diethyl ether as described previously (4 ). The dried extracts were reconstituted in a matrix recommended by the manufacturer.…”
Section: To the Editormentioning
confidence: 99%
“…None of the immunoassays investigated (Table 1) used an extraction step, as a prescribed procedure, before analysis. We extracted testosterone using diethyl ether as described previously (4 ). The dried extracts were reconstituted in a matrix recommended by the manufacturer.…”
Section: To the Editormentioning
confidence: 99%
“…In other studies, the performance of selected immunoassays using sera from individual donors and mass spectrometrybased (MS) assays as a comparative method was investigated [30,35,[38][39][40]. For most assays, the investigators observed high correlations between the MS assay and the immunoassays.…”
Section: Current Variability In T Measurementsmentioning
confidence: 99%
“…Researchers concerns about the quality of testosterone measurements have initiated recommendations to repeat measurements with more reliable assays on already completed epidemiological studies and clinical trials [29]. Others have recommended not using certain assays such as free testosterone analog assays [2,[30][31][32]. However, despite these recommendations, tests are still used that are unsuitable for addressing clinical and public health questions [1].…”
Section: Introductionmentioning
confidence: 99%
“…Testosterone assays have been 'under ¢re' for some time, 4--6 and concerted action is required to improve them. 7 …”
Section: Does This Cross-reactivity Matter?mentioning
confidence: 99%